Structural dynamic characterization of biobased micro aerial vehicles / Rubentheren Viyapuri - Rubentheren, Viyapuri (2013)
Micro Aerial Vehicle, MAVs is latest generation of aircraft inspired from micro natural fliers. Mimicking those fliers need extensive research and fine tools. Besides flight dynamics, propulsion system and structures integrity, wings plays a very important role in creating lifts and vortices to make a successful liftoff. MAV wings subjected to enormous level of mechanical stress due to flapping frequencies and posses a wide area to scope air. With all those bombardment, MAV wings should perform in a harmonize way with the stress being generated, yet the wing should be keep at minimum weight as possible. This research work is intended to investigate the mechanical properties of thin film PVA with biomimetic units drawn on the surface on the film for the application of MAV wing membrane. Biomimetic units grid, striation, spot were drawn on the surface of PVA thin film by means of heated geometry cutter. A control specimen named no pattern were then compared with the biomimetic specimen in terms of tensile testing for mechanical properties, DMA analysis for viscoelastic properties and DSC analysis for percentage of crystallinity. Result shows grid specimen exhibit highest level of mechanical properties and viscoelastic properties. This is due to the percentage of crystallinity formed in grid was the highest and thus elevate the mechanical properties of PVA thin film. Heated geometry cutter creates localized heat to melt the polymer and solidify quickly which crystallize the edge of the drawn pattern and in turn improve the mechanical properties when compared to pure PVA thin film.